(untitled) (Materiali di Estetica. Terza serie, 2025)
The aim of this article is to analyse the role of the musical performer, noting its particularities, and to present an hypothesis concerning the ideal status of the musical work of art. We will observe the development of musical notation, oriented towards an unattainable perfection, establishing its intrinsic limits, its vagueness and conventionality. We will try to delineate to what extent we can speak of the freedom of the performer and the functioning of the complex empathic relationship that the performer establishes with the author and the listener. Finally, we will see how Kantian aesthetic philosophy can offer support for our discussion.